2013
DOI: 10.2147/ijn.s43683
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of chitosan-PEG-TAT nanoparticles for the intracellular delivery of siRNA

Abstract: Recently, cell-penetrating peptides have been proposed to translocate antibodies, proteins, and other molecules in targeted drug delivery. The proposed study presents the synthesis and characterization of a peptide-based chitosan nanoparticle for small interfering RNA (siRNA) delivery, in-vitro. Specifically, the synthesis included polyethylene glycol (PEG), a hydrophilic polymer, and trans-activated transcription (TAT) peptide, which were chemically conjugated on the chitosan polymer. The conjugation was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Preclinical safety and efficacy testing of microbicide candidates involves a large number of in vitro , ex vivo , and in vivo assays and models. Here we demonstrated that chitosan-based nanoparticles showed no significant toxicity in rhesus monkeys, which is consistent with other modified chitosan nanoparticles for siRNA delivery [ 55 , 56 ]. Thus, the siRNA-based chlipid microbicides described in this study were subjected to a very cautious and rigorous preclinical evaluation to assess their efficacy in models used for microbicide development.…”
Section: Discussionsupporting
confidence: 88%
“…Preclinical safety and efficacy testing of microbicide candidates involves a large number of in vitro , ex vivo , and in vivo assays and models. Here we demonstrated that chitosan-based nanoparticles showed no significant toxicity in rhesus monkeys, which is consistent with other modified chitosan nanoparticles for siRNA delivery [ 55 , 56 ]. Thus, the siRNA-based chlipid microbicides described in this study were subjected to a very cautious and rigorous preclinical evaluation to assess their efficacy in models used for microbicide development.…”
Section: Discussionsupporting
confidence: 88%
“…For certain diseases, such as cancer, passive targeting based on an enhanced permeation and retention effect can increase tumor drug accumulation [113], however, the improvement is often moderate. Therefore, siRNA nanocarriers developed in recent years have often been functionalized with active-targeting moieties, such as mono-clonal antibodies, receptor substrates and cell-penetrating peptides [90,114116]. The advantage of this active-targeting strategy is illustrated in the study of asymmetric liposome particles, which were designed with the positive charges on the inner surface to minimize the nonspecific cellular uptake [114].…”
Section: Strategies To Overcome Nanotoxicity Of Sirna Carriersmentioning
confidence: 99%
“…Biopolymers have been used to encapsulate therapeutics in part due to their ease of use and their biocompatible nature [ 30 ]. Polymers used include alginate [ 31 , 32 ], heparin [ 33 , 34 ], chitosan [ 35 , 36 ], and carrageenan [ 37 , 38 ], among others. Alginate, a naturally derived polymer, is composed of varied amounts of β- d -mannuronate and α- l -guluronate residues linked by 1,4-glycosidic linkages [ 39 ] (M and G blocks, respectively).…”
Section: Introductionmentioning
confidence: 99%